Optimizing Natural Gas Liquid Recovery: Efficient and Cost-Effective Methods for Enhanced Performance (Global Journals of Research in Engineering, 2024)
The oil and gas industry a cornerstone of the modern economy for nearly a century and a half is now witnessing the full potential of the natural gas sector Historically natural gas has often been an unwanted byproduct of crude oil production frequently vented or flared However technological advancements are enabling more effective and economical methods for capturing processing transporting and utilizing this valuable resource This research crucial for the industry s future focuses on the challenges of safely processing storing and transporting natural gas while maximizing output particularly in the context of natural gas liquids NGLs The primary objective of this study is to explore various methods for enhanced NGL recovery from natural gas highlighting the growing demand for these valuable components Key findings indicate that several existing processes including absorption cryogenic separation and membrane technology offer significant potential for deep NGL recovery Membrane technology stands out due to its efficiency and cost-effectiveness These findings suggest that optimizing NGL recovery processes can play a crucial role in meeting the world s increasing demand for cleaner energy and specialty chemicals The recommendations for future research underscore the need for further exploration of membrane technology s application in NGL recovery and the importance of continued innovation in separation processes to enhance overall efficiency and sustainability in the natural gas industry
Keywords: natural gas liquids; NGL recovery; membrane technology; lean oil absorption; chemical impacts